Entrepreneurship Education Through Mobile Augmented Reality for Introducing SMEs in Higher Education - Situmorang, Robinson; Kustandi, Cecep; Maudiarti, Santi; Widyaningrum, Retno; Ariani, Diana (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Education is a place to introduce culture and micro, small and medium enterprises in areas far from the capital. In Technology Education Study Program, Universitas Negeri Jakarta has the vision to produce educators and education personnel in the field of learning to engineer based on academic principles and ethics. Engineering new media learning through augmented reality becomes a tool for lectures introducing SMEs. For this reason, researchers collaborated with material expert lecturers,  design experts,  media experts, and 30 students in developing augmented reality as a new learning application. The results of the review obtained from the instructional design experts were 3.20, material expert 3,30, and media experts 3.14. Based on the test results obtained from students in the one-to-one stage of 3.55; and at the small group stage of 3.23. Based on the results of the evaluation, it can be concluded that Augmented Reality can be implemented and used to introduce SMEs to college students. Students can use this product as material strengthening in engineering learning using new media applications